Noveleta's Fish Market by the Bay developing urban coasts through aquacultural fish ports and market tourism - De Guzman, Emily Jean S.
Fishing continues to be the main source of livelihood for many coastal communities in the Philippines. Due to rapid urbanization in the country however, many coastal communities are often left to fend for themselves as they compete against bigger fishing companies amidst the decline of fish populating poverty in these shoreline communities. While there have been efforts to promote the fishing industry in these communities, these facilities barely garner any type of traction, address the decline in fish population, or take into consideration the systems in place, ultimately damaging the marine and urban ecosystem further. This is the case of Noveleta, Cavite. It is endowed with a 15-kilometer-long shoreline overlooking Manila Bay and is caught in the middle of numerous municipalities and cities which contribute to its increasing urbanization. Its coastal communities continue to experience a decline in subsistence level due to climate change directly affecting fish catch and the rise in competition against bigger companies with more resources. This thesis explores the integration of aquacultural fish farms in the normal fish market and port setting as a way of promoting a more stable and sustainable fish catch along with tourism in the area. It aims to achieve this by exploring adaptive architectural interventions and solutions that focus on social, economic, and ecological dimensions within the functions of a fish market, hatchery, and port. The research delves into the study of the systems that contribute to the effectiveness and efficiency of these typologies to develop an aquaculture facility in Noveleta's urban setting integrating these three dimensions into one systematic output.